Supervision Mining System : Rekonstruksi Pengawasan Sektor Hulu Minyak dan Gas Bumi yang Berkeadilan Sosial di Indonesia - Nabila Aulia Rahma; Juan Maulana Alfedo; Liavita Rahmawati (Jurnal Hukum Lex Generalis, 2021)
The principle of people's welfare is implied in the fifth precept of Pancasila which reads "social justice for all Indonesian people". Pancasila is the philosophy of the state (Philosofische Gronslag) and a state policy that contains fundamental values that are the basis for the achievement of the Indonesian state. The state ideal contained in the preamble of the 1945 NRI Constitution shows the characteristics of the welfare state (Welfare State) that mandates the State to be responsible for the welfare of the people. This is confirmed in Article 33 of the 1945 NRI Constitution that the earth's water and natural wealth in it are controlled by the State and used as much as possible for the welfare of the people. The article then becomes a constitutional foundation as well as the direction of arrangements in the management of natural resources based on social justice to provide real added value to the national economy. As well as Oil and Gas (Migas) is a strategic natural resource as well as a vital commodity that controls the lives of many people and has an important role in the national economy so that its managers must provide prosperity and welfare of the people. One of the upstream oil and gas business activities that have an important role as a driver of the national economy is the upstream oil and gas sector. The upstream oil and gas sector will provide significant benefits if managed and supervised properly. In order to carry out these supervisions, the government established the Oil and Gas Implementing Agency (BP Migas) as the power holder of the upstream oil and gas sector. But after the issuance of the Constitutional Court decision No. 36 / PUU-X / 2012, BP Migas was dissolved because it was considered unconstitutional. As a result of the law in 2013, the Government established SKK Migas to carry out upstream management of Oil and Gas. But the existence of SKK Migas in practice does not guarantee the creation of more effective upstream oil and gas supervision. The disproportionate soaring cost recovery shows the weakness of SKK Migas in conducting supervision and control of the upstream oil and gas sector. Therefore, an effective supervision system is needed to increase the productivity of the upstream oil and gas sector and national welfare. Based on these problems, the author initiated a supervision mining system which is a new model of supervision that is ideal to accommodate the implementation of upstream oil and gas business activities based on the value of social justice.